1975
DOI: 10.1103/physrevlett.34.1330
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of One-Dimensional Plasmon Dispersion and Damping

Abstract: of remarkably reproducible thin potential wells and barriers, essentially rectangular and uniform to the order of a monolayer, can be created with molecular-beam epitaxy. The coupling behavior of the wells proves that synthetic superlattices can indeed be created. The molecularbeam-epitaxy technique for fabrication and the optical technique for energy-level determination should be applicable to additional configurations and compositions of interest for both basic and applied studies.We wish to acknowledge L. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 9 publications
8
18
1
Order By: Relevance
“…Further analyses of Williams and Bloch, as well as of Kahn et al, within the extended models [4,5] with two one-dimensional electron bands, each on a different type of chain, have predicted a second excitation. Williams and Bloch have found that the second coupled plasmon mode has been acoustic, but still both obtained modes have been placed above the electron-hole quasi-continuum in contrast to the experimental findings which did not resolve the two branches [2], whereas Kahn et al have shown that coupling between sublattice plasmons leads to the appearance of the acoustic collective mode in the narrow region between the quasi-continuums of two sublattices where its weak strength makes it unobservable in agreement with experiment.…”
Section: Introductioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Further analyses of Williams and Bloch, as well as of Kahn et al, within the extended models [4,5] with two one-dimensional electron bands, each on a different type of chain, have predicted a second excitation. Williams and Bloch have found that the second coupled plasmon mode has been acoustic, but still both obtained modes have been placed above the electron-hole quasi-continuum in contrast to the experimental findings which did not resolve the two branches [2], whereas Kahn et al have shown that coupling between sublattice plasmons leads to the appearance of the acoustic collective mode in the narrow region between the quasi-continuums of two sublattices where its weak strength makes it unobservable in agreement with experiment.…”
Section: Introductioncontrasting
confidence: 42%
“…Modes Ω 1 and Ω 2 can be directly associated with the optical data of TTF-TCNQ. Mode Ω 1 can be assigned to the excitation at ≈ 10 meV observed at 100K in the infrared measurements [6][7][8], while mode Ω 2 corresponds to the excitation at ≈ 0 75 eV [2]. The supporting reasons include the following: The measurements show [6,8] that the low-lying excitation at ≈ 10 meV disappears below 50 K, which is the temperature of the Peierls transition for TTF-TCNQ.…”
Section: Analysis and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The approach has been verified in [6,7], by assigning the renormalised plasmon to the excitation at 10 meV [2][3][4], while the renormalised dipolar mode is assigned to the excitation at 0.75 eV [1]. According to this approach, the origin of such a combination of collective modes is a strong threedimensional dipole Coulomb electron-electron interaction which leads to a strong coupling of initial intraband plasmons and interband dipolar modes.…”
Section: Introductionmentioning
confidence: 99%
“…Collective modes as low energy renormalised plasmon and high energy renormalised dipolar modes are the consequence of electronic correlations. Experimentally, collective modes have been observed in this material by electron energy-loss spectroscopy (EELS) [1] and by optical measurements [2][3][4].…”
Section: Introductionmentioning
confidence: 99%